2016
DOI: 10.3171/2015.6.jns1535
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-derived orphan receptor 1 transduces survival signals in neuronal cells in response to hypoxia-induced apoptotic insults

Abstract: C erebral hypoxia is commonly caused by traumatic brain injury (TBI) and brain tumors. A prospective study reported that almost half of patients with a severe head injury had epidemiologically experienced a period of hypoxia. 6 This low-oxygen condition can subsequently lead to brain edema and neurodegeneration. 30 To neurologically critically ill patients, cerebral hypoxia is further recognized as a major potential cause of secondary injury. 22 Clinically, hypoxia is highly associated with a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…In our present study, firstly, the effects of 6G on hypoxia-treated PC-12 cells were measured. In addition, caspases were activated in the process of apoptosis [19]. Autophagy is also a type of cell death which degrades and recycles long-lived or damaged proteins and cytoplasmic organelles by lysosomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, firstly, the effects of 6G on hypoxia-treated PC-12 cells were measured. In addition, caspases were activated in the process of apoptosis [19]. Autophagy is also a type of cell death which degrades and recycles long-lived or damaged proteins and cytoplasmic organelles by lysosomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…7B. Interestingly, we identified Nr4a subfamily ( Nr4a1/Nur77 and Nr4a3/Nor1 36, 37 ) which regulates apoptosis and inflammation was significantly decreased in HFD (Fig. 7B).…”
Section: Resultsmentioning
confidence: 80%
“…Release of mitochondrial cytochrome c to the cytoplasm can react with apoptotic protease-activating factor-1 (Apaf-1) and apoptosome to form a complex with an assistance of deoxyadenosine triphosphate [Jiang and Wang, 2000]. The multimeric cytochrome c-Apaf-1 complex can then trigger procaspase-9 into its activated form [Jiang and Wang, 2000;Ow et al, 2008;Chio et al, 2016]. In this study, we showed that dexmedetomidine reduced the reperfusion injuryinduced enhancement of caspase-9 protease activity in neuronal cells via suppressing cytochrome c release from mitochondria.…”
Section: Discussionmentioning
confidence: 93%